Xylem anatomy and hydraulic traits in Vitis grafted cuttings in view of their impact on the young grapevine decline - Battiston, Enrico; Falsini, Sara; Giovannelli, Alessio; Schiff, Silvia; Tani, Corrado; Panaiia, Roberta; Papini, Alessio; Di Marco, Stefano; Mugnai, Laura (Frontiers in Plant Science, 2022)
Grapevine grafting is an essential practice in viticulture and over the years, various bench grafting techniques have been developed to mechanize the nursery process and to increase the yield in number of viable cuttings. Bench grafting is a fundamental nursery practice that can potentially affect the quality of propagation material also in young decline associated to grapevine trunk diseases and has been recently reported to influence leaf symptoms development associated with diseases of Esca complex. The study aimed to investigate how three bench grafting methods (i.e. i) Omega graft as mechanical technique, ii) Whip and Tongue graft as manual technique and iii) Full Cleft graft as semi-mechanical technique can influence these phenomena. Specifically, the different methods were compared for their effect on the anatomical development of the grafting point and the functionality of the xylem, also considering two factors: the grapevine cultivar (Cabernet Sauvignon, Glera and Teroldego) and the scion/rootstock diameter (thin and large). Observations by light microscopy on the anatomical evolution and measurements on the xylem morphology and hydraulic traits were correlated with the grafting methods and the investigated varieties. The anatomical observations revealed that the mechanical (Omega) and semi-mechanical (Full Cleft) grafting methods have a faster callusing response while the manual technique (Whip and Tongue) has a slower but greater vascularization of the differentiated callus. Significant differences between cultivars and/or grafting types were also detected in necrotic area on the grafted tissues. Statistical analysis of the grapevine vessels suggested differences in xylem parameters between cultivars, while grafting type had no significant effects. On the other hand, the grafting type significantly affected the intrinsic growth rate. The study confirms the potential incidence of lesions and dysfunctionalities correlated with the grafting method applied, which can potentially induce grafted vine declines in vineyards due to the necrotic area detected on the grafted tissues.